Towards an explanatory framework for national level maternal health policy agenda item evolution in Ghana: an embedded case study - Koduah, A.; Agyepong, I.A.; van Dijk, H. (Health Research Policy and Systems, 2018)
Background Understanding decision-making processes that influence the fate of items on the health policy agenda at national level in low- and middle-income countries is important because of the implications for programmes and outcomes. This paper seeks to advance our understanding of these processes by asking how and why maternal health policy agenda items have fared in Ghana between 1963 and 2014. Methods The study design was a single case study of maternal health agenda evolution once on a decision pathway in Ghana, with three different agenda items as sub-units of analysis (fee exemptions for maternal health, free family planning and primary maternal health as part of a per capita provider payment system). Data analysis involved chronologically reconstructing how maternal health policy items evolved over time. Results The fate of national level maternal health policy items was heavily influenced by how stakeholders (bureaucrats, professional bodies, general public and developmental partners) exercised power to put forward and advocate for specific ideas through processes of issues framing within a changing political and socioeconomic context. The evolution and fate of an agenda item once on a decision pathway involved an iterative process of interacting drivers shaping decisions through cycles of ‘active’ and ‘static’ pathways. Items could move from ‘active’ to ‘static’ pathways, depending on changing context and actor positions. Items that pursued the ‘static’ pathway in a particular cycle fell into obscurity by a process that could be described as a form of ‘no decision made’ in that an explicit decision was not taken to drop the item, but neither was any policy content agreed. Low political interest was exhibited and attempts to bring the item back into active decision-making were made by actors mainly in the bureaucratic arena seeking and struggling (unsuccessfully) to obtain financial and institutional support. Policy items that pursued ‘active’ pathways showed opposite characteristics and generally moved beyond agenda into formulation and implementation. Conclusion Policy change requires sustaining policy agenda items into formulation and implementation. To do this, change agents need to understand and work within the relevant context, stakeholder interests, power, ideas and framing of issues.
Keywords: Decision pathway; Policy actors; Policy agenda; Policy evolution; Policy fate; Power; Ghana; Maternal health